A lightweight privacy‐preserving scheme with data integrity for smart grid communications. (28th May 2015) - Bao, Haiyong; Chen, Le
Summary: Smart grid, deemed as the next generation of power grid, can efficiently monitor, control, and predicate energy generation and consumption. However, the frequent collection of users' consumption information in smart grid may reveal user's privacy, and the tampering of smart grid communication may also impair the data integrity, subsequently affecting the precise monitoring and controlling at the control center. In this paper, to address the aforementioned challenges, we propose a lightweight data report scheme for smart grid communications, which can achieve privacy preservation and data integrity simultaneously. Specifically, an efficient pseudonym identity‐based privacy‐preserving report approach is proposed for the control center to obtain the fine‐grained usage data of all the users while protecting user's privacy. An online / off‐line hash tree‐based mechanism is also designed to check and assure data integrity of communications. Because of the shifting of most time‐consuming computations to off‐line phase, the online process is very fast and efficient by performing merely the lightweight bottom‐up hash tree verifications to check all users' data integrity concurrently. Furthermore, a topology‐independent data report architecture is also structured, which is adaptable for dynamic residential users to spontaneously form clusters and efficiently report data in flocks. Extensive performance evaluation demonstrates that the proposed scheme can achieve less communication overhead and dramatically reduce computational cost in comparison with the existing schemes. Copyright © 2015 John Wiley & Sons, Ltd.